Frozen shoulder contracture syndrome: manipulation under anesthesia or physical therapy? - Christopher Felipe Cereceda Muriel; Denisse Elizabeth Concha Valdebenito; Dennis González Valencia (Medisur)
Frozen shoulder contracture syndrome is a pathological condition that involves contracture of the joint capsule of the glenohumeral joint, generating pain, restriction of both active and passive range of motion, and impaired function. Various treatments have been proposed and investigated to solve this condition. On the one hand, there are surgical treatments, and on the other, non-surgical ones. Regarding surgical procedures, arthroscopic capsular release and manipulation under anesthesia stand out. The latter consists of mobilizing the shoulder in different directions to break the adhesions of the joint capsule, all this under anesthesia. In relation to the most used non-surgical treatments, there is the prescription of medications, corticosteroid injections, arthrographic hydrodilation and physical therapy. The modalities of physical therapy are an option of easy access, low cost and with varied options. Despite multiple alternatives being presented, there is no consensus on which is the best treatment option, and specifically it remains unclear whether manipulation under anesthesia is a better option than physiotherapy treatment.